Педагогический опыт формирования успешной личности ребёнка с использованием компьютерных игр - Ryzhenkova E. A. (Education, innovation, research as a resource for community development, 2024)
Computer games attract an increasing number of children and teenagers. The use of computer games in education has already shown itself on the positive side. To date, numerous educational programs are being created. The use of computer games can also be effective in shaping a child's personality. This aspect is not actively reflected in pedagogical practice, however, it is concomitant in teaching children using computer games
Keywords: педагог; развитие; компьютерные игры; teacher; development; личность педагога; игры; педагогический опыт; успешная личность; games; successful personality; computer games; personality of a teacher; pedagogical experience